SOME COMPARATIVE OPINIONS REGARDING THE WORKING OF FIBERS AND MATRIX ON AXIAL STRESS LIMIT. MATRIX WITH LONGER FIBER EXTENSIONS - RADU I. IATAN; ANDREEA - SILVIA NITU; MIHAI STATESCU; ELENA SURDU; DANA-CLAUDIA FARCAS - FLAMAROPOL; MELANIA CORLECIUC (MITUCA); COSMIN CIOCOIU (Journal of Engineering Studies and Research, 2022)
This paper falls within the current scientific and technical research concerns related to structures made of long fiber composite materials. An essential problem is the co-operation of the matrix material with that of the fibers in the composite layers under the action of external loads, until the structure is damaged. In the present case, the case is taken into account if the material of the matrix is characterized by elongations superior to those of the fibers, so that they will break before the damage of the matrix. The linear-elastic behavior of the fibers is considered until their rupture and, obviously, the destruction of the composite.